2007
DOI: 10.1002/mnfr.200600258
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the developing female reproductive system by phytoestrogens: Genistein as an example

Abstract: Studies in our laboratory have shown that exposure to genistein causes deleterious effects on the developing female reproductive system. Mice treated neonatally on days 1-5 by subcutaneous injection of genistein (0.5-50 mg/kg) exhibited altered ovarian differentiation leading to multioocyte follicles (MOFs) at 2 months of age. Ovarian function and estrous cyclicity were also disrupted by neonatal exposure to genistein with increasing severity observed over time. Reduced fertility was observed in mice treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 95 publications
2
50
1
Order By: Relevance
“…Current findings showed a decrease in BW at puberty onset and a tendency for an increase in duration of first estrus in gilts fed the diet without soya compared with gilts fed the commercial soya diet, but there was no effect of added genistein. This is contrary to our expectation because mice treated neonatally with genistein generally show an increased length of the estrous cycle (review by Jefferson et al, 2007) and accelerated onset of puberty (Lewis et al, 2003). This discrepancy between our results and those reported in mice could be due to the difference in age at treatment (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Current findings showed a decrease in BW at puberty onset and a tendency for an increase in duration of first estrus in gilts fed the diet without soya compared with gilts fed the commercial soya diet, but there was no effect of added genistein. This is contrary to our expectation because mice treated neonatally with genistein generally show an increased length of the estrous cycle (review by Jefferson et al, 2007) and accelerated onset of puberty (Lewis et al, 2003). This discrepancy between our results and those reported in mice could be due to the difference in age at treatment (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…It is well documented that neonatal exposure of mice to genistein disrupts ovarian function during adulthood and reduces fertility (review by Jefferson et al, 2007). To the best of our knowledge, only two studies looked at the effects of phytoestrogens on reproduction in swine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect of estrogen underscores the need for further research on the effect of endocrine disruptors - environmental and dietary compounds that act like hormones - in reproductive diseases. Along these lines, increasing evidence from rodent studies indicates that neonatal exposure to genistein, the phytoestrogen found in soy, disrupts normal reproduction (30)(31)(32)(33)(34)(35)(36). The effects of phytoestrogens and other estrogen-like compounds on the reproductive tract, fertility, and reproductive cancers are not well understood.…”
Section: Introductionmentioning
confidence: 99%